Surrounding Rock Control Technology When the Longwall Face Crosses Abandoned Roadways: A Case Study. (17th November 2021) - Jiang, Zhenpeng; Wang, Fangtian; Miao, Kaijun; Cao, Qinghua
Abstract : When a working face is crossing the abandoned roadways, problems such as roof subsidence, rock fracture, and instability will occur, resulting in widespread roof fall and rib spalling, which seriously affect safe and efficient mining on the working face. In this paper, the no. 23 coal pillar working face of Juji coal mine is taken as the engineering background, a mechanical model of crossing the abandoned roadways is constructed aimed at the problem of the working face crossing the abandoned roadway group, the collapse of the abandoned roadway roof is analyzed, a scheme of crossing the abandoned roadways is designed, and the development law of the stress and plastic zone after the reinforcement scheme is stimulated and analyzed. The results show that when the working face advances to the abandoned roadway, key block B crosses the abandoned roadway and the solid coal to form a "cross-roadway long key block." It is calculated that the minimum support resistance required for the abandoned roadway is 6700 kN. Based on the results of numerical comparison, it is concluded that filling wood pile when the working face passes through the roof abandoned roadway and adding anchor cables for reinforcement support when the working face crosses the coal seam abandoned roadway effectively reduce the stress concentration of surrounding rocks, decrease the development of the plastic zone, and achieve safe and efficient mining when the working face crosses the abandoned roadways.